The vegetarian pantry : fresh and modern recipes for meals without meat - Coker, Chloe; Montgomery, Jane (United Kingdom : Ryland Peters & Small, 2013)
You don't have to eat meat and fish to enjoy delicious food. Learn how to create stunning dishes using fresh vegetables and fruit with this collection of modern vegetarian recipes. Breakfast and Brunch features French Toast Stuffed with Bananas and Berry Compote - perfect for lazy Sunday mornings. Appetizers and Snacks such as Spicy Corn Cakes with Avocado Salsa are perfect for sharing. Learn how to make Dips, Salsas and Sauces with the freshest ingredients - try Apple, Celery and Mint Salsa. Soups and Salads includes a hearty Warm Salad of Pearl Barley with Mushrooms and Walnuts. Seasonal vegetables come into their own in Main Dishes. Try Carrot and Leek Tart with a Balsamic Reduction. Enjoy sumptuous desserts such as Individual Hazelnut Meringues stuffed with Cream and Seasonal Fruit. With plenty of tips on what to stock in your pantry and how to store vegetarian staples such as grains, beans and pulses, The Vegetarian Pantry includes everything you need for the very best vegetarian cooking.
Introduction -- Breakfast and brunch -- Small bites -- Dips, salsas and sauces -- Soups and salads -- Main dishes -- Sweet treats -- Index -- Acknowledgements.
Includes index.
Keywords: VEGETARIAN COOKING